2010
DOI: 10.1371/journal.pone.0012883
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antiviral Roles of a Fish β-Defensin Expressed Both in Pituitary and Testis

Abstract: Defensins are a group of cationic peptides that exhibit broad-spectrum antimicrobial activity. In this study, we cloned and characterized a β-defensin from pituitary cDNA library of a protogynous hermaphroditic orange-spotted grouper (Epinephelus coioides). Interestingly, the β-defensin was shown to be dominantly expressed in pituitary and testis by RT-PCR and Western blot analysis, and its transcript level is significantly upregulated in reproduction organs from intersexual gonad to testis during the natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 70 publications
1
65
0
2
Order By: Relevance
“…BD-1 is generally expressed in epithelial cells of the gastrointestinal and broncho-respiratory tract, tissues involved in host defense, and only one study so far has reported BD-1 expression in the posterior lobe of the pituitary (neurohypophysis) of the fish orange-spotted grouper, where it plays a still unidentified role (46).…”
Section: Discussionmentioning
confidence: 99%
“…BD-1 is generally expressed in epithelial cells of the gastrointestinal and broncho-respiratory tract, tissues involved in host defense, and only one study so far has reported BD-1 expression in the posterior lobe of the pituitary (neurohypophysis) of the fish orange-spotted grouper, where it plays a still unidentified role (46).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the remaining pAbs were trout CAMP specific. Western blot was performed to analyze the reactivity of the pAbs with trout CAMPs as previously described (25).…”
Section: Peptide Synthesismentioning
confidence: 99%
“…Significantly, some novel interferon-inducible genes have been found [121], and their functional roles and signaling pathways have been well understood in fish [122][123][124]. Additionally, several candidate genes, such as PKR [125], PKR-like (or called PKZ) [126], β-Defensin [127], TRBP [128], C-type lectin [129], Enzyme E2 [130], MDA5 and LGP2 [131], have been revealed to play crucial roles in the antiviral defense response of fish and shrimp.…”
Section: Disease Resistance Trait and Candidate Disease Resistance-rementioning
confidence: 99%